Arch-AdSenNets: an architecture for inter-working MANET with wireless sensor and actor networks. (6th November 2008) - Le-Trung, Quan; Kotsis, Gabriele
This paper proposes an architecture, namely Arch-AdSenNets, for inter-working mobile ad-hoc networks (MANETs) with wireless sensor and actor networks. We lay out requirements, discuss possible solutions and propose a network model within Arch-AdSenNets for the collaboration of MANET nodes and actors. It is formulated as a multi-objective optimisation problem, solving theoretically and centrally by the micro-genetic algorithm. Distributed and heuristic algorithms have also been developed, consisting of two phases: set-up and negotiation. The former is used to initially distribute MANET nodes over event areas, while the latter is used to redistribute MANET nodes depending on the existing and new coming events. We have implemented the distributed algorithm into ns-2, piggy backing over the optimised link-state routing protocol. Simulation results show that resources of MANET nodes, spending on processing detected events (utility), and their resources, spending on moving to event areas (cost), converge to optimal results found by the micro-genetic algorithm.